Environment-friendly composite salt grouting material

By preparing an environmentally friendly composite salt grouting material including acrylic acid, methacrylic acid and other environmentally friendly, it solves the problems of strong toxicity and environmental threats in polyurethane grouting materials, and provides solutions that are non-toxic, low viscosity, high permeability and rapid curing. The solution is suitable for tunnel projects and basements, improving construction safety and quality.

CN119241190APending Publication Date: 2025-01-03SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411606288.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing polyurethane grouting materials contain highly toxic low-flash point solvents and plasticizers, which lead to environmental and human health threats. The fire prevention requirements at the construction site are high, and there is a risk of major accidents.

Method used

Use environmentally friendly composite salt grouting materials, including acrylic acid, methacrylic acid, magnesium oxide, calcined kaolin, calcium carbonate, N-hydroxyethyl acrylamide, butyl acrylate, hydroquinol, diethylene triamine, defoaming agent and Dispersants, prepared by specific mixing and stirring steps, form non-toxic, low viscosity, high permeability and fast curing materials.

Benefits of technology

It realizes a non-toxic, low viscosity, high permeability and fast curing environmentally friendly composite salt grouting material, with good bonding performance and elasticity, suitable for tunnel projects and basements, ensuring construction safety and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241190A_ABST
    Figure CN119241190A_ABST
Patent Text Reader

Abstract

The invention provides an environment-friendly composite salt grouting material, and belongs to the technical field of grouting material preparation. The environment-friendly composite salt grouting material is prepared from the following components in parts by mass: 180 to 200 parts of acrylic acid, 200 to 210 parts of methacrylic acid, 80 to 100 parts of magnesium oxide, 150 to 180 parts of calcined kaolin, 220 to 250 parts of calcium carbonate, 20 to 30 parts of N-hydroxyethyl acrylamide, 6 to 10 parts of butyl acrylate, 0.5 to 1 part of hydroquinone, 12 to 15 parts of diethylenetriamine, 2 to 5 parts of a de-foaming agent and 3 to 7 parts of a dispersing agent. The obtained environment-friendly composite salt grouting material is non-toxic, does not damage the health of users and is environment-friendly, and the adopted acid and alkali have good chemical resistance, are not affected by biological invasion, and are extremely low in viscosity and good in permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting material preparation, and in particular to an environmentally friendly composite salt grouting material. Background Art

[0002] With the rapid development of my country's economy, energy shortage has prompted the vigorous development of coal mining industry. A number of large-scale, high-yield and high-efficiency underground mines have been put into production. The depth of traditional coal mines has increased, but it has also brought a series of problems. In many underground projects, concrete is prone to defects and cracks due to various stresses during long-term use, which greatly reduces the mechanical properties and causes significant losses to the national economy.

[0003] Due to its superior performance, polyurethane grouting materials are increasingly widely used in water conservancy, hydropower, tunnels, subways, mines, civil air defense, industrial and civil construction projects, especially in foundation reinforcement, leak plugging, curtain anti-seepage and crack repair in engineering construction.

[0004] Document CN92106672.4 discloses a method for preparing polyurethane type grouting material, which is to use isocyanate residual liquid and hydroxyl compound as two components, directly and evenly mix them according to proportion, and then grouting is carried out, and then the hydroxyl compound component can be used as a single component, or it can be used as the main body and various auxiliary agents or additives are added to share, and these hydroxyl compounds can be polyether, polyester, polybutadiene, alkyd resin, polyacrylic resin, etc. Document CN200810052170.9 discloses a method for preparing a polyurethane chemical grouting single liquid grouting chemical material, but its preparation process is divided into three steps, first preparing a terminal hydroxyl polyurethane prepolymer, then using it as a raw material to prepare a hydrophilic polyurethane prepolymer, and finally adding a diluent, a foam stabilizer, a catalyst and a plasticizer to the hydrophilic polyurethane prepolymer in step 2 and stirring to make it uniform. The process is long and complicated, and the product contains a large amount of (more than 20%) low boiling point solvent acetone, and acetone is a restricted chemical, which not only greatly reduces the safety performance of the product, but also puts forward extremely high qualification requirements for the manufacturer's raw material procurement and product transportation. Document CN200910101168.0 discloses a high flash point (flash point>100°C) environmentally friendly water-soluble polyurethane chemical grouting material. It is characterized by being composed of isocyanate, hydrophilic polyether, plasticizer, high boiling point composite solvent (mixture of composite fatty acid esters) and foam stabilizer. It is suitable for anti-seepage treatment of dams and other building foundations, subways, tunnel water inrush treatment, etc. The addition of the solvent at the end of the preparation process requires the addition of the high boiling point solvent and foam stabilizer after the prepolymer reaction is completed.

[0005] As can be seen from the above, the prepolymer polyurethane grouting materials in the prior art need to be diluted with acetone, xylene and other low-flash point flammable solvents and plasticizers that are highly toxic to the environment and human body, so as to improve the flow and diffusion properties of the slurry. Since it contains low-flash point flammable liquids, the flash point is generally lower than 61°C, so the fire prevention requirements at the construction site are very high, and a major accident will occur if you are not careful. Furthermore, since these solvents and plasticizers themselves are highly volatile and toxic, they pose a great threat to the health of people in underground projects such as subways, tunnels, and culverts.

[0006] Therefore, it is of great practical significance to provide an environmentally friendly grouting material that can replace traditional polyurethane grouting materials. Summary of the invention

[0007] The purpose of the present invention is to provide an environmentally friendly composite salt grouting material, aiming to solve the technical problem of replacing the polyurethane grouting materials in the prior art that are highly toxic and unfriendly to the environment.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides an environmentally friendly composite salt grouting material, comprising the following components in parts by weight:

[0010] 180-200 parts of acrylic acid, 200-210 parts of methacrylic acid, 80-100 parts of magnesium oxide, 150-180 parts of calcined kaolin, 220-250 parts of calcium carbonate, 20-30 parts of N-hydroxyethyl acrylamide, 6-10 parts of butyl acrylate, 0.5-1 part of hydroquinone, 12-15 parts of diethylenetriamine, 2-5 parts of defoaming agent and 3-7 parts of dispersant.

[0011] Furthermore, the calcium carbonate is heavy calcium carbonate.

[0012] Furthermore, the defoaming agent is ethylene bisstearamide and paraffin.

[0013] Furthermore, the dispersant is polycarboxylate ammonium salt.

[0014] The present invention also provides a method for preparing the environmentally friendly composite salt grouting material described in the above technical solution, comprising the following steps:

[0015] Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture:

[0016] Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture;

[0017] adding N-hydroxyethyl acrylamide and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture;

[0018] A dispersant, a defoamer, calcined kaolin and calcium carbonate are added to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material.

[0019] Furthermore, the particle size of the calcined kaolin is 1200-1300 meshes.

[0020] Furthermore, the particle size of the calcium carbonate is 800-1000 meshes.

[0021] Furthermore, the temperature of the second mixing is 40-60°C.

[0022] The present invention also provides the use of the environmentally friendly composite salt grouting material described in the above technical solution or the environmentally friendly composite salt grouting material obtained by the preparation method in tunnel engineering or basement.

[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0024] The present invention adopts environmentally friendly and non-toxic raw material components to obtain an environmentally friendly composite salt grouting material; secondly, the composite salt grouting material of the present invention has extremely low viscosity and good permeability, and can penetrate into a gap with a width of 0.1 mm; the curing time is adjustable, and the fast curing only takes 20 seconds, while the slow curing can be greater than 10 minutes; it has high elasticity, an elongation of up to 200%, does not shrink when drying, and slightly expands when exposed to water; it has good bonding performance with a concrete base surface, and the bonding strength is equivalent to the strength of its own gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the preparation method of the environmentally friendly composite salt grouting material of the present invention. DETAILED DESCRIPTION

[0026] The present invention provides an environmentally friendly composite salt grouting material, comprising the following components in parts by weight:

[0027] 180-200 parts of acrylic acid, 200-210 parts of methacrylic acid, 80-100 parts of magnesium oxide, 150-180 parts of calcined kaolin, 220-250 parts of calcium carbonate, 20-30 parts of N-hydroxyethyl acrylamide, 6-10 parts of butyl acrylate, 0.5-1 part of hydroquinone, 12-15 parts of diethylenetriamine, 2-5 parts of defoaming agent and 3-7 parts of dispersant.

[0028] The environmentally friendly composite salt grouting material of the present invention preferably includes the following components in parts by weight: 180-200 parts of acrylic acid, 200-210 parts of methacrylic acid, 80-100 parts of magnesium oxide, 150-180 parts of calcined kaolin, 220-250 parts of calcium carbonate, 20-30 parts of N-hydroxyethyl acrylamide, 6-10 parts of butyl acrylate, 0.5-1 part of hydroquinone, 12-15 parts of diethylenetriamine, and 2 parts of defoaming agent. ~5 parts and 3-7 parts of dispersant; more preferably 180-190 parts of acrylic acid, 200-205 parts of methacrylic acid, 80-90 parts of magnesium oxide, 150-160 parts of calcined kaolin, 220-230 parts of calcium carbonate, 20-25 parts of N-hydroxyethyl acrylamide, 6-8 parts of butyl acrylate, 0.5-0.8 parts of hydroquinone, 12-13 parts of diethylenetriamine, 2-3 parts of defoamer and 3-5 parts of dispersant.

[0029] The raw material components adopted in the present invention are all environmentally friendly materials, which are harmless to human body and environment, and the obtained composite salt grouting material is an environmentally friendly product.

[0030] In the present invention, the calcium carbonate is preferably heavy calcium carbonate.

[0031] In the present invention, the defoaming agent is preferably ethylene bisstearamide and paraffin.

[0032] The present invention preferably uses ethylene bisstearamide and paraffin as defoaming agents. The defoaming agent can reduce the viscosity of the grouting material and improve its fluidity. In some cases where grouting over a long distance or passing through a small pipe is required, the fluidity of the grouting material is particularly important. The addition of the defoaming agent can make the grouting material flow more smoothly and ensure the grouting effect.

[0033] The present invention does not impose any particular limitation on the usage ratio of ethylene bisstearamide and paraffin wax, and any ratio or any ratio known to those skilled in the art may be used.

[0034] In the present invention, the dispersant is preferably a polycarboxylate ammonium salt.

[0035] The present invention preferably uses polycarboxylate ammonium salt as the dispersant of the present application, weakens and dismantles the clustering connection between particles in the grouting material, releases free water, thereby changing the properties of the hydration product, and dispersing the particles, which helps the grouting material to maintain better uniformity and stability during the grouting process and avoid agglomeration or precipitation. The addition of the dispersant can reduce the plastic viscosity and yield value of the grouting material, which is beneficial to the flow and construction of the grouting material. By reducing the viscosity, the grouting material can more easily fill the structural gaps and form a dense and uniform grouting layer, which can not only improve the grouting efficiency, but also ensure the grouting quality. The present invention does not specifically limit the type of polycarboxylate ammonium salt, and those familiar to those skilled in the art can be used.

[0036] The present invention also provides a method for preparing the environmentally friendly composite salt grouting material described in the above technical solution, comprising the following steps:

[0037] Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture:

[0038] Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture;

[0039] adding N-hydroxyethyl acrylamide and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture;

[0040] A dispersant, a defoamer, calcined kaolin and calcium carbonate are added to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material.

[0041] In the first mixing of the present invention, the usage ratio of water to acrylic acid is preferably 1.2 to 1.5:1.

[0042] In the present invention, the particle size of the calcined kaolin is preferably 1200-1300 mesh, and more preferably 1200-1250 mesh.

[0043] In the present invention, the particle size of the calcium carbonate is preferably 800-1000 mesh, more preferably 800-900 mesh.

[0044] In the present invention, the temperature of the second mixing is preferably 40 to 60°C, more preferably 40 to 50°C.

[0045] The present invention also provides the use of the environmentally friendly composite salt grouting material described in the above technical solution or the environmentally friendly composite salt grouting material obtained by the preparation method in tunnel engineering or basement.

[0046] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] (1) adding 0.5 parts of hydroquinone, 6 parts of butyl acrylate, 200 parts of methacrylic acid, 180 parts of acrylic acid and 216 parts of water into a reaction kettle, mixing and stirring to obtain a first mixture;

[0050] (2) slowly adding 80 parts of magnesium oxide to the first mixture, mixing, and stirring to obtain a second mixture. During the addition of magnesium oxide, the temperature of the reactor was controlled to be 40° C.;

[0051] (3) adding 20 parts of N-hydroxyethyl acrylamide and 12 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;

[0052] (4) Add 3 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of paraffin, 150 parts of calcined kaolin and 220 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1200 mesh, and the heavy calcium carbonate has a particle size of 800 mesh. After uniform mixing, the environmentally friendly composite salt grouting material is obtained.

[0053] Example 2

[0054] (1) adding 0.8 parts of hydroquinone, 8 parts of butyl acrylate, 205 parts of methacrylic acid, 190 parts of acrylic acid and 228 parts of water into a reaction kettle, mixing and stirring to obtain a first mixture;

[0055] (2) slowly adding 90 parts of magnesium oxide to the first mixture, mixing, and stirring to obtain a second mixture. During the addition of magnesium oxide, the temperature of the reactor was controlled to be 50° C.;

[0056] (3) adding 25 parts of N-hydroxyethyl acrylamide and 13 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;

[0057] (4) Add 5 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of paraffin, 150 parts of calcined kaolin and 220 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1250 mesh, and the heavy calcium carbonate has a particle size of 900 mesh. After uniform mixing, the environmentally friendly composite salt grouting material is obtained.

[0058] Example 3

[0059] (1) adding 1 part of hydroquinone, 10 parts of butyl acrylate, 210 parts of methacrylic acid, 180 parts of acrylic acid and 216 parts of water into a reaction kettle, mixing and stirring to obtain a first mixture;

[0060] (2) slowly adding 80 parts of magnesium oxide to the first mixture, mixing, and stirring to obtain a second mixture. During the addition of magnesium oxide, the temperature of the reactor was controlled to be 60° C.;

[0061] (3) adding 30 parts of N-hydroxyethyl acrylamide and 12 parts of diethylenetriamine to the second mixture for a third mixing, and mixing evenly to obtain a third mixture;

[0062] (4) Add 3 parts of polycarboxylate ammonium salt dispersant 5027, 2 parts of paraffin, 150 parts of calcined kaolin and 250 parts of heavy calcium carbonate to the third mixture for a fourth mixing, wherein the calcined kaolin has a particle size of 1300 mesh, and the heavy calcium carbonate has a particle size of 1000 mesh. After uniform mixing, the environmentally friendly composite salt grouting material is obtained.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An environmentally friendly composite salt grouting material, characterized in that: The invention comprises the following components in parts by weight: 180-200 parts of acrylic acid, 200-210 parts of methacrylic acid, 80-100 parts of magnesium oxide, 150-180 parts of calcined kaolin, 220-250 parts of calcium carbonate, 20-30 parts of N-hydroxyethyl acrylamide, 6-10 parts of butyl acrylate, 0.5-1 part of hydroquinone, 12-15 parts of diethylenetriamine, 2-5 parts of defoaming agent and 3-7 parts of dispersant.

2. The environmentally friendly composite salt grouting material according to claim 1, characterized in that: The calcium carbonate is heavy calcium carbonate.

3. The environmentally friendly composite salt grouting material according to claim 1, characterized in that: The defoaming agents are ethylene bis stearamide and paraffin.

4. The environmentally friendly composite salt grouting material according to claim 1, characterized in that: The dispersant is polycarboxylate ammonium salt.

5. The method for preparing the environmentally friendly composite salt grouting material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Hydroquinone, butyl acrylate, methacrylic acid, acrylic acid and water are first mixed and stirred to obtain a first mixture: Slowly adding magnesium oxide to the first mixture for second mixing, and stirring to obtain a second mixture; adding N-hydroxyethyl acrylamide and diethylenetriamine to the second mixture for a third mixing to obtain a third mixture; A dispersant, a defoamer, calcined kaolin and calcium carbonate are added to the third mixture for a fourth mixing to obtain the environmentally friendly composite salt grouting material.

6. The method for preparing the environmentally friendly composite salt grouting material according to claim 5, characterized in that: The particle size of the calcined kaolin is 1200-1300 meshes.

7. The method for preparing the environmentally friendly composite salt grouting material according to claim 5, characterized in that: The particle size of the calcium carbonate is 800-1000 meshes.

8. The method for preparing the environmentally friendly composite salt grouting material according to claim 5, characterized in that: The temperature of the second mixing is 40-60°C.

9. Use of the environmentally friendly composite salt grouting material according to any one of claims 1 to 4 or the environmentally friendly composite salt grouting material obtained by the preparation method according to any one of claims 5 to 8 in tunnel engineering or basement.